Computational analysis of protein-ligand interaction by targeting a cell cycle restrainer. (April 2023) - Singh, Rahul; Purohit, Rituraj
Highlights: Exhaustive computer simulations are implemented for identification of CDK4 inhibitor. The newly reported potent inhibitors have a more active inhibitory ability towards CDK4 than palbociclib. The measured ligand efficiency and estimated binding affinity are higher than the standard. The stable binding conformations are favorable to the binding affinity of selected ligands. Abstract: Background and objective: The cyclin-dependent kinases 4/6 (CDK4/6) are among the most crucial controllers of the cell cycle, and their abnormal activity may induce uncontrolled cell multiplication, leading to cancers. The FDA currently approved three CDK4/6 inhibitors, however, they are associated with a variety of side effects. Thus it is required to design/develop novel potent and safe CDK4/6 inhibitors. Methods: In the present work, we furnished an integrated in-silico approach followed by steered molecular dynamics (SMD) simulations to identify molecules that can be developed into novel CDK4/6 inhibitors. Results: Out of thirty-two 3-methyleneisoindolin-1-one molecules we selected top three M18, M24, and M32 molecules as potential drug candidates based on their respective interaction energies. According to the robust 250 ns MD simulations and thermodynamic free energy, M24 was the best molecule in comparison to palbociclib. In SMD, M24 required ∼205.587 kJ/mol/nm external pulling force, while palbociclib needed ∼160.97 kJ/mol/nm to dissociate from the binding pocket of the CDK4. Conclusions: The high pulling force required for M24 dissociation from the binding site denotes stronger binding with CDK4. Therefore, M24 offers the possibility of a critical starting structure in developing effective CDK4 inhibitors. Graphical abstract: Image, graphical abstract